Effectiveness of Evidence-Based Pediatric Nursing Practices on Clinical and Developmental Outcomes in Children: A Comprehensive Systematic Review - Uma Shende; Vijayalakshmi.K; Shobhita K Das (International Journal of Evidence Based Nursing And Practices, 2026)
Evidence-based pediatric nursing practices are essential for improving health outcomes among children by integrating clinical expertise with the best available research evidence and patient-centered care approaches. This systematic review examines the effectiveness of evidence-based pediatric nursing interventions on clinical and developmental outcomes in children across various healthcare settings. A comprehensive search of databases including PubMed, CINAHL, Scopus, and the Cochrane Library was conducted for studies published between 2016 and 2026. A total of 78 studies met the inclusion criteria and were analyzed using a narrative synthesis approach. The findings demonstrate that evidence-based nursing interventions significantly improve clinical outcomes such as reduction in hospital-acquired infections, enhanced pain management, decreased length of hospital stay, and improved recovery rates. Furthermore, developmental outcomes including cognitive, emotional, and behavioral development were positively influenced through interventions such as early stimulation, family-centered care, and therapeutic communication. Nurse-led initiatives such as infection control protocols, developmental care strategies, and technology-based interventions including electronic health records and simulation training contributed to improved care quality and patient safety. Despite these benefits, challenges such as limited resources, inadequate training, and variability in implementation remain barriers to the widespread adoption of evidence-based practices.
Keywords: Child Health; Child development; Developmental outcomes; Evidence-Based Practice; Evidence-based care; Family-centered care; Nursing Interventions; Pediatric nursing; Pediatric patient safety; clinical outcomes